An Analysisi Of Coping Mechanism of Peter Parker in Spiderman No Way Home - Alif Hamdani (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study aims to analyze the coping mechanisms employed by Peter Parker in Spider-Man: No Way Home. The research focuses on identifying the types of coping mechanisms represented through Peter Parker's thoughts, emotions, dialogues, and actions, as well as examining their functions in responding to traumatic experiences. This study applies a qualitative descriptive method using a psychological approach. The primary data were collected from the dialogues, scenes, and actions of Peter Parker in Spider-Man: No Way Home. The analysis is based on Lazarus and Folkman's theory of coping mechanisms, which classifies coping into Problem-Focused Coping and Emotion-Focused Coping. The findings reveal that Peter Parker employs both types of coping mechanisms throughout the film. Problem-focused coping is reflected in his efforts to solve the multiverse crisis, cure the villains, and take responsibility for the consequences of his decisions. Meanwhile, emotion-focused coping is demonstrated through his expressions of grief, anger, guilt, emotional support-seeking behavior, and eventual acceptance after experiencing traumatic events, particularly the death of Aunt May. Furthermore, the study finds that Peter Parker's coping mechanisms serve three major functions: managing stress and trauma, maintaining psychological stability, and facilitating personal growth. These findings indicate that coping mechanisms play a significant role in Peter Parker's psychological development, enabling him to overcome emotional distress and mature as an individual. Therefore, this study contributes to literary and film studies by providing a deeper understanding of how psychological coping strategies are represented in contemporary superhero films through the portrayal of fictional characters